The impact of non-communicable diseases on employment status in South Africa - Nozuko Lawana; Kapingura Forget Mingiri; Asrat Tsegaye (Cogent Economics & Finance, 2023)
The study examines the impact of non-communicable diseases (NCDs) and employment status in South Africa utilising the National Income Dynamics Study longitudinal data from 2008 to 2017. The Generalized Linear Latent and Mixed Methods (GLLAMM) were employed to fit the multinomial logit model with correlated random intercept over panel multinomial logit without random effects to control for unobserved heterogeneity between individuals or intercepts. The empirical results indicate that the significant impact of NCDs on employment status differs by gender. NCDs were found to be most threatening to women employment status. The odds of women being economically inactive in the labour market are highly associated with NCDs. Further, having multiple NCDs also significantly increases the women's probability of being economically inactive population relative to being employed. The results highlight the necessity for undertaking a massive awareness campaign regarding the prevention and control of NCDs, especially among women.
Keywords: 330; employment status; GLLAMM; multinomial regression; Non-communicable diseases; South Africa